Family-Based Islamic Religious Education in Parenting Practice in Early Childhood Education - Mohammad Akmal Haris (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
Islamic religious education in early childhood requires continuity of values between home and school because the family plays the role of the first educational environment. This study aims to describe the implementation of family-based Islamic religious education in parenting practices in Sang Cipta Rasa Flagship Kindergarten, including value strengthening strategies, home-school consistency, impact on child development, and contemporary challenges. The research uses a qualitative approach with a case study design. The research subjects included school principals, classroom teachers, and parents who were selected purposively. Data were collected through semi-structured interviews, participatory observations, and analysis of parenting program documents and school-parent communication. Data analysis is carried out by thematic analysis, and the validity of the data is maintained through triangulation, member checking, peer discussion, and trace audits. The results of the study show that family-based Islamic religious education is carried out through a systematic home-school partnership in the form of religious parenting programs, routine communication, and guidelines for habituating values at home. The Islamic parenting pattern of parents tends to be empathic-dialogical with an emphasis on example, habituation, and warm communication. The consistency of home-school values contributes to the stability of children's religious behavior and the strengthening of moral, social, and emotional development (manners, discipline, empathy, and self-control). Key challenges include limited parental time, variations in religious literacy, and exposure to digital media. The study concludes that the collaborative-integrative home-school model is effective in strengthening the internalization of Islamic values in early childhood, with the need to strengthen parenting assistance and active digital mediation.